Design of Highly Efficient Semitransparent Perovskite/Organic Tandem Solar Cells - Rossi, Daniele; Forberich, Karen; Matteocci, Fabio; Der Maur, Matthias Auf; Egelhaaf, Hans-Joachim; Brabec, Christoph; Di Carlo, Aldo (Solar RRL, 2022)
Solar cells transparent in the visible range are highly requested for integration in see-through photovoltaic (PV) applications such as building glass façades or greenhouse roofs. The development of advanced transparent PV can fully exploit the tandem technology where the top cell absorbs the near-ultraviolet solar spectrum while the bottom one absorbs the near-infrared part. Herein, a possible implementation of this tandem PV paradigm, namely, the tandem structure composed of a high-bandgap halide perovskite solar cell and a low-bandgap organic solar cell, is considered. Electro-optical simulation results based on parameters calibrated on experimental data show that an efficiency of 15% can be achieved with an average visible transmittance above 50%. This can be obtained considering the halide perovskite with mixed chlorine and bromine anions, a nonfullerene-based bulk heterojunction, a well-calibrated light management, and a three-terminal configuration of the tandem.
CRIS-Team Scopus Importer:2022-07-08
Keywords: organic solar cells; pervoskite solar cells; solar cell simulations; tandem perovskite/organic solar cells; transparent solar cells